2007
DOI: 10.1210/en.2006-0989
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Matrix Metalloproteinase-9 Mediates the Inhibition of Myogenic Reactivity in Small Arteries Isolated from Rats after Short-Term Administration of Relaxin

Abstract: During pregnancy and chronic relaxin administration to nonpregnant rats (for days), vascular MMP (matrix metalloproteinase)-2 is increased and mediates renal vasodilation, hyperfiltration, and inhibition of myogenic reactivity of small renal arteries. However, the renal vasodilatory actions of relaxin also occur after only several hours of hormone administration to nonpregnant rats, and we hypothesized a pivotal role for vascular MMP-2. Accordingly, we used gelatin zymography, which reveals not only vascular M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 34 publications
(70 reference statements)
4
66
1
1
Order By: Relevance
“…Thus, a stiffer large artery in senescent SHRs is largely attributable to increased collagen content in the vascular matrix, and relaxin improves arterial compliance largely through its collagen-lowering action. Reduction in vascular collagen by relaxin treatment is most likely attributable to increased breakdown of collagen after increment in matrix metalloproteinase levels, as shown by studies from Jeyabalan et al 27 We did not determine matrix metalloproteinase levels, considering the fact that aorta samples were collected 7 days after termination of relaxin treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a stiffer large artery in senescent SHRs is largely attributable to increased collagen content in the vascular matrix, and relaxin improves arterial compliance largely through its collagen-lowering action. Reduction in vascular collagen by relaxin treatment is most likely attributable to increased breakdown of collagen after increment in matrix metalloproteinase levels, as shown by studies from Jeyabalan et al 27 We did not determine matrix metalloproteinase levels, considering the fact that aorta samples were collected 7 days after termination of relaxin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular actions of relaxin have been well described. 1 Conrad and colleagues 1,7,10,26,27 have conducted a series of studies documenting vasodilatation and arterial pressurelowering action of relaxin of exogenous or endogenous sources. Relaxin levels in pregnant rodents increase markedly together with the development of more compliant arteries, leading to the notion that endogenous relaxin plays a key role in the hemodynamic adjustment during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies showed that the 'C' to 'T' substitution at À1562 position increases MMP-9 expression. 17 However, the (CA) 14 allele causes a 50% reduction in MMP-9 promoter activity as compared with the (CA) 21 . 18,19 Interestingly, these polymorphisms may affect drug responses 20 and both polymorphisms have been associated with PE or GH, 21,22 thus suggesting that MMP-9 genetic variations may predispose to hypertensive disorders of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Specifically, MMP-9 may be involved in placental and uterine arterial remodeling 11,12 and in the control of the vascular tone. 13,14 In addition, there is evidence that MMPs interact with oxidative stress and inflammatory mediators contributing to the endothelial dysfunction of PE patients. 15 Therefore, the involvement of MMPs in the vascular alterations of hypertensive disorders of pregnancy may aggravate the lack of responses to antihypertensive therapy in some patients.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, MMP-2 and MMP-9 can acutely enhance vascular tone through the cleavage of vasoactive peptides such as adrenomedullin, calcitonin gene-related peptide and big endothelin-1 [16,[33][34][35]. Another non-ECM acute action of MMPs and ADAMs is shedding of membrane-anchored ligands of receptors such as epidermal growth factor (EGF) and platelet-derived growth factor (PDGF) to transactivate intracellular signaling of growth via the MAPK cascade.…”
Section: Cleavage Of Receptor Ligandsmentioning
confidence: 99%